Bureaucracy and administrative development in Bangladesh and Nigeria: a comparative analysis - Islam, Rafiqual (2005)
This paper makes a comparative analysis of the bureaucracy and administrative development of Bangladesh and Nigeria. The study finds some commonalities of the bureaucratic behaviors of Bangladesh and Nigeria that help to clarify some common features of bureaucracy in developing countries. Although the study of bureaucracies of Bangladesh and Nigeria attempts to highlight some common features of bureaucracies in developing nations, it also provides insights into explaining some potential differences between the bureaucracies and administrative systems of the two developing nations. The study also helps explain the role of bureaucracies in the administrative development of Bangladesh and Nigeria. -Reproduced.
Keywords: Corruption - Nigeria; Corruption - Bangladesh; Public administration - Nigeria; Public administration - Bangladesh; Bureaucracy - Nigeria; Bureaucracy - Bangaldesh; Bureaucracy